Correlates of HIV Risk Reduction Self-Efficacy among Youth in South Africa - Julia Louw; Karl Peltzer; Witness Chirinda (The Scientific World Journal)
Even though a decline in HIV prevalence has been reported among South African youth 15–24 from 10.3% in 2005 to 8.6% in 2008, the prevalence remains disproportionately high for females overall in comparison to males. This study examines factors associated by HIV risk reduction self-efficacy of South African youth as part of an evaluation of the impact of loveLife, a youth focused HIV prevention programme. A cross-sectional population-based household survey was conducted with persons of ages 18 to 24 years in four selected provinces in South Africa. Among female respondents (), factors associated with high self-efficacy in the adjusted model were having a low HIV risk perception, HIV/AIDS stigma, ever using drugs, and having life goals. Male respondents () with high self-efficacy were more likely to have been tested for HIV, have concurrent sexual partners, have had a transactional sex partner in lifetime, a low HIV risk perception, difficulty in having condoms, agreed with coercive sex, high relationship control, and had loveLife face-to-face programme participation. The factors identified with high self-efficacy and HIV-sexual risk behaviour may be considered to strengthen youth HIV prevention programmes in South Africa.